Hubungan antara kerja rumah dengan pencapaian akademik dalam kalangan pelajar dari kelas premier di dua buah sekolah menengah - Yeo , Kee Jiar (2011)
Homework has become an important component in schooling system in Malaysia. Besides this, homework is also an essential tool contributing towards higher achievement. This research is aimed to study the relationship between homework with students’ achievement in the subjects of Mathematics, English, and History among the form two premier students at Sekolah Menengah Kebangsaan Taman Mutiara Rini and Sekolah Menengah Kebangsaan Sri Skudai, Johor Bahru. In this research, the researcher focused on three factors, which include time spent, types of homework, and teacher supervision. The samples in this study were selected from two form two premier classes at SMK Sri Skudai and class at SMK Taman Mutiara Rini. Questionnaire was chosen by the researcher as the instrument to investigate the outcome of this study. This questionnaire consists of 2 sections. Section A includes the demographic items, students’ achievement, and time management. Section B includes 30 questions on the types of homework and teachers’ supervision on homework. The reliability of this instrument is ? = 0.929. The students’ result in end-year examination was used as students’ achievement in this study. In analyzing the data, researcher used two types of analysis: descriptive and inference statistic (Pearson correlation). Overall, the majority of students tend to have high achievement (60 – 79 %). The findings of this study showed significant correlation at medium level was found in two aspects: (1) teacher’s supervision during homework was assigned in Mathematics homework; and (2) teacher’s supervision after homework was assigned in Mathematics homework.